Chapter 7 – Size and reproduction: yield per recruit models - Santos, Jorge (Septentrio Educational, 2015)
QUESTIONS ASKED What are the bases of the traditional regulations of effort and gear in fisheries? What are the trade-offs between fishing early or late on the reproductive potential of the stocks? How certain is the advice, and what are the risks? Yield pr recruit R-based R-script YR I PR by projection contour F tc R-script YR II by projection single tc (F and f based) R-script YR III PR by projection Monte Carlo Risk single F tc